Cultural Disparities in the Use of Prescription and Nonprescription Medications Among Midlife Women in Israel. (July 2017) - Lerner-Geva, Liat; Blumstein, Tzvia; Boyko, Valentina; Farhi, Adel; Benyamini, Yael
The study aimed to examine differences in medication use among midlife women from different cultural origins and to identify socio-demographic, health, and lifestyle characteristics associated with prescribed and non-prescribed medication use. Face-to-face interviews with women aged 45–64 years were conducted during 2004–2006 within three population groups: long-term Jewish residents (LTJR), immigrants from the former Soviet Union after 1989, and Arab women. The survey instrument included current use of medications and way of purchasing (with/without prescription). The level of prescribed and non-prescribed medication use was categorized as taking none, taking 1–2, and taking 3 or more medications. The rates of medication use were 59.5% for prescribed medication and 47% for non-prescribed medications. Differences between the minority groups and LTJR were observed mainly for cardiovascular, vitamins, supplements, and hormonal medications. The analyses showed significantly lower use of prescribed medications among immigrants and of non-prescribed medications among Arab women after taking into account health and socioeconomic indicators. Increased use of prescribed and non-prescribed medications was associated with worse health status and older age. Education was associated with increased use of non-prescribed medications. The disparities in pharmaceutical care may be linked to barriers in access to health care and to cultural preferences among minorities.